In vivo composition of the mitochondrial nucleoid in mice - García-Villegas, Rodolfo; Odenthal, Franka; Giannoula, Yvonne; Bonekamp, Nina A.; Kühl, Inge; Park, Chan Bae; Spåhr, Henrik; Motori, Elisa; Levander, Fredrik; Larsson, Nils-Göran (Biochimica et biophysica acta. Molecular cell research, 2025)
Mitochondrial DNA (mtDNA) is compacted into dynamic structures called mitochondrial nucleoids (mt-nucleoids), with the mitochondrial transcription factor A (TFAM) as the core packaging protein. We generated bacterial artificial chromosome (BAC) transgenic mice expressing FLAG-tagged TFAM protein (Tfam-FLAGBAC mice) to investigate the mt-nucleoid composition in vivo. Importantly, we show that the TFAM-FLAG protein is functional and complements the absence of the wild-type TFAM protein in homozygous Tfam knockout mice. We performed immunoprecipitation experiments from different mouse tissues and identified 12 proteins as core mt-nucleoid components by proteomics analysis. Among these, eight proteins correspond to mtDNA replication and transcription factors, while the other four are involved in the mitoribosome assembly. In addition, we used the Tfam-FLAGBAC mice to identify ten proteins that may stabilize TFAM-FLAG upon depletion of the mitochondrial RNA polymerase despite the absence of mtDNA and induction of the LONP1 protease. Finally, we evaluated the changes in mt-nucleoids caused by very high levels of TFAM unraveling nine interactors that could counteract the high TFAM levels to maintain active mtDNA transcription. Altogether, we demonstrate that the Tfam-FLAGBAC mice are a valuable tool for investigating the mt-nucleoid composition in vivo.
Online verfügbar: 15. April 2025, Artikelversion: 28. April 2025
Gesehen am 07.07.2025